Paleocene origin of the cockroach families Blaberidae and Corydiidae: Evidence from Amur River region of Russia - Vršanský, Peter; Vidlička, Ľubomír; Barna, Peter; Bugdaeva, Eugenia; Markevich, Valentina (Zootaxa, 2013)
Morphna paleo sp. n., the earliest winged representative of any living cockroach genus and the earliest representative of the family Blaberidae, is described from the Danian Arkhara-Boguchan coal mine in the Amur River region (Russian Far East). The branched Sc and A suggest Ectobiidae (=Blattellidae) probably is not the ancestral family because Blaberidae were derived directly from the extinct family Mesoblattindae. The associated Danian locality Belaya Gora yielded Ergaula stonebut sp. n., the earliest record of the family Corydiidae. Both species belong to genera codominant in the Messel locality, thus validating their dominance in early Cenozoic assemblages.